Verification of Crack Width Evaluation in Fiber-Reinforced Cementitious Composite Reinforced with Various Types of Fiber-Reinforced Polymer Bars - Hideto Sasaki; Helen Negash Shiferaw; Toshiyuki Kanakubo (Fibers)
This study aims to verify the adaptability of a crack width evaluation method for fiber-reinforced cementitious composite (FRCC) proposed by the authors to various combinations of fiber-reinforced polymer (FRP) bars and FRCCs. As this evaluation method requires bond constitutive laws between FRP bars and FRCC, bond tests between FRP and FRCCs were conducted. The FRP and FRCC combinations used in the bond tests were spiral-type CFRP and GFRP bars with PVA-FRCC, as well as strand-type CFRP bars with aramid–FRCC. The maximum bond stress tended to increase as the rib–height ratio of the spiral-type bars increased. When the rib–height ratio increased by 50%, the maximum bond stress of the CFRP and GFRP bars increased by 11% and 33%, respectively. For aramid–FRCC, the average maximum bond stress in the FRCC with a 0.25% volume fraction was 1.67 times that in mortar, and that in 0.50% was 2.01 times that in mortar. The bond constitutive laws were modeled using the trilinear model. Verifications of the method’s adaptability were conducted using tension tests on prisms made of spiral-type CFRP and GFRP bars with PVA-FRCC. As a result of the tension tests, when the FRP strain reached approximately 0.3%, the crack width was about 0.2 mm for CFRP bars and about 0.1 mm for GFRP bars. Verifications were also conducted using four-point bending tests on strand-type CFRP bar beams with aramid–FRCC. The crack width at the same FRP strain tended to become smaller as the fiber volume fraction of FRCC increased. When the FRP strain reached approximately 0.2%, the average crack width of the mortar specimen was around 0.25 mm, whereas it was about 0.15 mm in FRCC with a 0.25% volume fraction and about 0.10 mm at 0.5%. The test results for FRP strain versus crack width relationships were compared with the calculations using the crack width prediction formula. The test results and calculation results were in good agreement.